Women Issues In Indie Work - Nor Hasimah Ismail; Melor Fauzita binti Md. Yusoff; Rafizah Mohd Rawian; Mohamad Syawal Narawi (Proceedings of The ICECRS, 2017)
The novel creation has been growing since ancient times until now. Indie's work is the latest masterpiece of the novel. This work is rather free and relaxed, even loaded with implicit and explicit elements. This study will examine the novel of Seronok on the issues and create conflicts. The problems that Rozilla had to do were to differentiate between desires, disagreements, inconsistencies and a sense of discontent that created action. The resulting conflict is a manifestation of dissatisfaction when an opinion to uphold justice is not accepted. However, the help of fellow human beings has solved the problems.